2021
DOI: 10.5194/os-17-975-2021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dense-water flow over a sloping bottom on open-sea circulation: laboratory experiments and an Ionian Sea (Mediterranean) example

Abstract: Abstract. The North Ionian Gyre (NIG) displays prominent inversions on decadal scales. We investigate the role of internal forcing induced by changes in the horizontal pressure gradient due to the varying density of Adriatic Deep Water (AdDW), which spreads into the deep layers of the northern Ionian Sea. In turn, the AdDW density fluctuates according to the circulation of the NIG through a feedback mechanism known as the bimodal oscillating system. We set up laboratory experiments with a two-layer ambient flu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 40 publications
(56 reference statements)
3
23
0
Order By: Relevance
“…Interannual and decadal variabilities are related to changes of the thermohaline properties and circulation regimes such as Eastern Mediterranean Transient (EMT), Western Mediterranean Transition (WMT), and Adriatic-Ionian Bimodal Oscillating System (BiOS) [37][38][39][40][41]. The WMT can be defined as a climate shift, which changed the basic structure and properties of the intermediate and deep layers of the western Mediterranean, with an abrupt increase in temperature, salinities, and densities [39,42]; it affects the characteristics of the water exiting the Gibraltar Strait.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interannual and decadal variabilities are related to changes of the thermohaline properties and circulation regimes such as Eastern Mediterranean Transient (EMT), Western Mediterranean Transition (WMT), and Adriatic-Ionian Bimodal Oscillating System (BiOS) [37][38][39][40][41]. The WMT can be defined as a climate shift, which changed the basic structure and properties of the intermediate and deep layers of the western Mediterranean, with an abrupt increase in temperature, salinities, and densities [39,42]; it affects the characteristics of the water exiting the Gibraltar Strait.…”
Section: Introductionmentioning
confidence: 99%
“…This event influences not only the deep layer but also the entire water column and the circulation structures of the Eastern Mediterranean [19,44]. The BiOS is a feedback mechanism, driven by the difference in salinity between the salty and warmer waters originating in the eastern Mediterranean and the less saline AW entering from the Sicily Channel [39,41,45,46], that is accredited to having led to the quasi-decadal reversal of the Northern Ionian Gyre (NIG) from anticyclonic to cyclonic and vice-versa. Evidence of the importance of this mechanism was obtained by dimensional analysis and laboratory experiments [39][40][41]45,46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first theory relates NI current reversals to changes in the wind stress curl [9][10][11] ; the second relates current reversals of the Ionian near-surface circulation to baroclinic (internal) vorticity production, induced by changes in the horizontal pressure gradient due to injections of Adriatic Deep Water (AdDW) 12 . Rubino et al 13 and Gačić et al 14 , relying on tank experiments and numerical modeling, demonstrated that the polarity switch of the near-surface circulation in the NIG can be indeed induced by the injection of dense water on a sloping bottom.The two theories offer an explanation about the physics underlying the BiOS paradigm, but both have flaws. Specifically, the first theory, although based on the most natural approach to explain the inversion of the…”
mentioning
confidence: 99%
“…The complex thermohaline circulation of the SAP (Figure 4.7.1) is driven by the interaction between different processes: the wintertime dense water formation events that occur through open-ocean convection (Gačić et al 2002); the inflow of fresher water from the northern Adriatic rivers (Vilibić et al 2013) and of dense water produced in the northern Adriatic (Bensi et al 2013); and the inflow/outflow of surfaceintermediate/dense water masses from/to the Otranto Channel (Yari et al 2012). Moreover, thermohaline and biogeochemical properties in the SAP are closely related to the periodic reversal (from anticyclonic to cyclonic and vice-versa) of the Northern Ionian Gyre (NIG; Gačić et al , 2021Menna et al 2019;Rubino et al 2020) on a quasi-decadal temporal scale Mihanović et al 2021). NIG reversals affect the water mass distribution among the Eastern Mediterranean sub-basins (Gačić et al 2011;Bessieres et al 2013;Reale et al 2017;Notarstefano et al 2019), in turn influencing the thermohaline properties of the whole Mediterranean on decadal and multi-decadal scales (Gačić et al 2013;Schroeder et al 2017;Menna et al 2022).…”
Section: Introductionmentioning
confidence: 99%